The Effect of Work-Life Balance, Compensation, and Work Stress on Turnover Intention with Job Satisfaction as an Intervening Variable in PO Bejeu Jepara - Hesti Futukhatun Nu’ma; Bayu Kurniawan; Noni Setyorini (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2026)
This study aims to examine the effects of work-life balance, compensation, and job stress on turnover intention, with job satisfaction as a mediating variable at PO Bejeu Jepara. Using a sample of 146 drivers and covariance-based SEM analysis with AMOS 22, the findings show that work-life balance and compensation have a significant negative effect on turnover intention, while job stress has a significant positive effect. Job satisfaction itself has a significant negative effect on turnover intention. Work-life balance and compensation have a significant positive effect on job satisfaction, but job stress does not have a significant effect. Furthermore, work-life balance influences turnover intention indirectly through job satisfaction, whereas compensation and job stress do not show a significant mediating effect through job satisfaction.